Sexual dimorphism for juvenile body weight in chickens divergently selected for 8-week body weight - Siegel, Paul B.; Honaker, Christa F. (Frontiers in Physiology, 2025)
There is a dearth of literature on the genetics of sexual dimorphism for juvenile body weight in meat-type chickens given its biological and economic relevance. Herein, we report the sexual dimorphism for 4- and 8-week body weights in White Plymouth Rock chicken lines that have undergone 67 generations of selection. Fluctuations in the degree of dimorphism occurred across generations, with greater dimorphism and less variation at 8 weeks than 4 weeks. Over the 67 generations, there was a significant decrease in the degree of dimorphism in the high line, with no changes in the low line. It is very difficult to genetically modify sexual dimorphism in a particular population using the currently available conventional tools, and nature possesses homeostatic mechanisms that maintain stasis in a population.